Sleep apnea plays a more important role on sleep N3 stage than chronic tinnitus in adults. Issue 34 (26th August 2022) - Tseng, Hsin-Hao; Hwang, Sheng-Wei; Hwang, Shang-Rung; Hwang, Juen-Haur
Abstract : Sleep apnea is negatively associated with N3 sleep in children. However, the association between tinnitus and sleep N3 stage was still inconclusive. We aimed to clarify the relationship between sleep apnea, chronic tinnitus, and sleep N3 stage in adults. Clinical and overnight polysomnography data of 2847 adults were collected retrospectively. Univariate and multivariate linear regression was used to test the impacts of sleep apnea indices and chronic tinnitus on the percentage of sleep N3 stage in all adults. Univariate linear regression analysis showed that sleep apnea indices, chronic tinnitus, age, sex, hypertension, diabetes mellitus, dyslipidemia, subjective insomnia, sleep efficiency, and rapid eye movement sleep were significantly associated with sleep N3 stage. However, multivariate linear regression showed that apnea–hyponea index, but not chronic tinnitus, has a significant negative association with the percentage of sleep N3 stage. Sleep apnea plays a more important role on sleep N3 stage than chronic tinnitus in adults.